Clinical Evaluation of Budesonide Therapy in Patients with Microscopic Colitis - A Retrospective Cohort Study - Bottema, Indy; Oirschot, Juliette van; Gilissen, Lennard PL (Archives of Clinical and Medical Case Reports, 2025)
Objectives: Budesonide is the first-choice therapy to achieve and maintain clinical remission in microscopic colitis (MC), however the optimal duration of therapy is still unclear. This study aimed to evaluate budesonide therapy in a single-center cohort with long-term follow-up, focusing on relapse rates and steroid dependency. Methods: All patients with histologically proven MC at the Catharina Hospital between February 2009 and May 2018 were retrieved from the Dutch histopathology database. Patients were categorized into different budesonide regimen groups. The primary outcome was medication free clinical remission related to budesonide therapy. Second, duration and dosage of budesonide therapy and immuno-modulating therapy in refractory MC was evaluated. Results: In total 89 MC patients were included. Median follow-up was 34.8 months (IQR 17.6-63.0). Fourteen patients (16%) achieved clinical remission either without medication or following non-steroid therapy. Seventy-five patients (84%) were treated with budesonide, of whom 27 (36%) with a single and 17 (19%) with intermittent budesonide courses. Following induction therapy, 69 patients (92% achieved remission. However, during long term follow-up 42 (56%) experienced at least one relapse, indicating the need for maintenance treatment in many cases. Only 27 (36%) of all 75 budesonide treated patients were able to maintain budesonide free clinical remission. Forty-one (54.7%) had chronic/ relapsing MC and seven (9.3%) needed immunomodulators. Conclusions: Budesonide is effective as induction therapy for patients with MC. Many patients need budesonide-maintenance, in contrary to the treatment guidelines. We suggest guiding budesonide therapy by clinical symptoms rather than by a fixed time frame.